PROTECTION OF HUMAN RIGHTS IN LAW ENFORCEMENT ACTIVITIES: CONCEPT, TYPES AND NATURE OF INTERNATIONAL LEGAL STANDARDS - VOLOSHCHUK, OKSANA (Ehrlich’s Journal, 2024)
The article examines the concept and essence of international standards of law enforcement. It has been clarified: international standards of law enforcement activity are model, model rules recorded in international legal acts, are based on respect for human rights, other universal democratic values and guide law enforcement agencies to their observance in the performance of their official duties. The main features of these standards are outlined: fundamentality, general democracy, dynamism, recommendability, universal recognition, practicality, optimality. It was also clarified: due to the dynamic nature of international standards of law enforcement activity, it is not possible to determine their number, there is only an indicative list; due to the multifaceted nature of law enforcement activities, there are many subcontracted international standards of law enforcement activities in various areas of fighting, countering and preventing crime. The conclusion was made: the development and adoption of international standards is a general democratic dynamic process that affects the global legal development as a whole due to the standardization of the approaches of states to the regulation of important social problems, including in the field of law enforcement, the unification of model norms on human rights at the international level and harmonization and improvement of national legislation in various legal systems in particular. International law enforcement standards are based on these general standards and should be imbued with the idea of anthropocentrism.